A case of infection and severe soft tissue loss of the elbow. Planning surgical treatment in compliance with good clinical-care practices and medico-legal implications. - Amadei, Federico; Bruno, Maurilio Cosimo; Romano', Carlo; Basile, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Soft tissue loss around  the elbow, with tendons, nerves and bone exposure,  represents a challenging condition, often requiring a complex and accurate surgical reconstruction. Inadequate repair of soft tissue defects may in fact compromise further reconstructive orthopedic procedures, including  osteosynthesis and joint replacement. A correct reparative sequence of these lesions usually starts with an appropriate debridement and removal of all non-viable and infected tissues, followed by soft tissues management through plastic and reconstructive techniques.Here we present a case report, showing a successful surgical solution, using a local muscular flap. The results are discussed in light of their functional and medico-legal implications, considering the frequent occurrence of partial functional recovery, the disabling impact on social and work activities and the aesthetic sequelae of these lesions, even in spite of a successful treatment.